2000
DOI: 10.1002/sdr.201
|View full text |Cite
|
Sign up to set email alerts
|

Not only the tragedy of the commons: misperceptions of feedback and policies for sustainable development

Abstract: The article summarizes key insights from four laboratory experiments to study renewable resource management. The commons problem, which is widely held to be the cause of mismanagement of common renewable resources, was ruled out by the design of the experiments. Still the participants overinvested and overutilized their resources. The explanation offered is systematic misperceptions of stocks and flows and of nonlinearities. The heuristics that people apply are intendedly rational for static, flow resources, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 28 publications
2
83
1
4
Order By: Relevance
“…In order to address this issue, researchers would need to be able to conceptualize and measure resilience as the distance of a particular social-ecological system from its tipping point, so that agents could be able to prevent the crisis before it happens. Identifying a priori the vulnerability of the system to an incremental effectsinduced crises is extremely difficult however (Moxnes 2000). Initially, the amount of CDH harvested increases in response to increasing the number of boats, which decrease the population of mature CDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address this issue, researchers would need to be able to conceptualize and measure resilience as the distance of a particular social-ecological system from its tipping point, so that agents could be able to prevent the crisis before it happens. Identifying a priori the vulnerability of the system to an incremental effectsinduced crises is extremely difficult however (Moxnes 2000). Initially, the amount of CDH harvested increases in response to increasing the number of boats, which decrease the population of mature CDH.…”
Section: Discussionmentioning
confidence: 99%
“…More often than not, users of a common-pool resource system fail to recognize that their systems are falling into a collapse trajectory (Moxnes 2000). The experience that people have before crossing the tipping point is likely to misguide them when the crisis arrives.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has shown that human beings have difficulty drawing valid inferences about the relationship between the underlying structure of a complex system and its behavior (e.g., Dörner 1997;Moxnes 2000;Sterman 1989Sterman , 2002. People tend to underestimate the effects of delays, ignore the role of feedback, and rely on linear associations when drawing inferences about the behavior of complex systems.…”
Section: Computer Simulationmentioning
confidence: 97%
“…The maximum accumulated appropriation that permits a community to reach round T , is T t=1 n i=1 x it = F 0 +T gne c+g points, 24 which corresponds with a maximum 23 Using a linear growth function for the resource stock implies that the Pareto efficient solution leads to defer consumption, however it had the advantage to ease the understanding of the consequences of agents actions on the evolution of the resource stock (Moxnes 2000(Moxnes , 2004. 24 We determine this maximum accumulated appropriation from (A.2) in the paper assuming that F T = 0.…”
Section: Benchmark 4: Limit Strategymentioning
confidence: 99%